ATP-driven calcium transport in membrane vesicles of Streptococcus sanguis. - Houng, H S (1986)
Calcium transport was investigated in membrane vesicles prepared from the oral bacterium Streptococcus sanguis. Procedures were devised for the preparation of membrane vesicles capable of accumulating 45Ca2+. Uptake was ATP dependent and did not require a proton motive force. Calcium transport in these vesicles was compared with 45Ca2+ accumulation in membrane vesicles from Streptococcus faecalis and Escherichia coli. The data support the existence of an ATP-driven calcium pump in S. sanguis similar to that in S. faecalis. This pump, which catalyzes uptake into membrane vesicles, would be responsible for extrusion of calcium from intact cells.